2018
DOI: 10.1371/journal.pone.0208465
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics based clustering of globin family members

Abstract: A methodology to cluster proteins based on their dynamics’ similarity is presented. For each pair of proteins from a dataset, the structures are superimposed, and the Anisotropic Network Model modes of motions are calculated. The twelve slowest modes from each protein are matched using a local mode alignment algorithm based on the local sequence alignment algorithm of Smith–Waterman. The dynamical similarity distance matrix is calculated based on the top scoring matches of each pair and the proteins are cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The PDB file B-factor values are replaced by the RDSS and best dynamically matching areas are visualized by the B-factor coloring option of the used viewer, Pymol [54]. The ability of the current algorithm to identify local dynamics similarity is demonstrated in our recent papers, where we present a detailed dynamical comparison between myoglobin and hemoglobin [46] and show its ability to perform dynamics-based clustering [55].…”
Section: Methodsmentioning
confidence: 99%
“…The PDB file B-factor values are replaced by the RDSS and best dynamically matching areas are visualized by the B-factor coloring option of the used viewer, Pymol [54]. The ability of the current algorithm to identify local dynamics similarity is demonstrated in our recent papers, where we present a detailed dynamical comparison between myoglobin and hemoglobin [46] and show its ability to perform dynamics-based clustering [55].…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the elastic network approach does not require molecular dynamics but rather relies on a static structure and spring force constants derived empirically from a database of crystallographic B-factors. This instrument is well suited to exploring force propagation in biomolecules and had been used to address the properties of a variety of systems such as cooperativity in protein dimers and tetramers, 49,50 signal transduction in ion channels, 51 and transcription factors bound to their DNA targets. 52 Naked 12-mer DNA (PDB entry 355D 53 ) demonstrated good correlations of vibrational movements propagating along each strand for approximately two or three nucleotides except for the terminal parts (Figure S1).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…24 Still aiming at a protein family, Tobi developed an ENM-based method to make a function classification for globin family members based on their dynamics' similarity. 25 Besides, in 2020, an insightful review by Bahar et al revealed the evolutionary constraints on structure dynamics of a protein family to achieve the required functions: the slowest motion modes are conserved by a protein family for the common function; the low-to-intermediate frequency (LTIF) modes reflect the function specificity across family members; the fastest frequency modes ensure the core stability, which is the basics of functional specialization. 26 Besides the ENM model, currently, the protein structure network (PSN) has been widely used in the studies of protein folding, allosteric transition, and key site prediction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Combined with the ENM model, perturbation response scanning (PRS) analysis was proposed to obtain protein dynamics and allosteric properties, and currently, the method has been widely applied to identify the key residues in allosteric control and long-range communications for large protein assemblies. , Additionally, a systematic method of approach was developed by Bahar et al for characterizing the shared (signature) as well as unique structural and dynamic properties of a protein family using a combination of structure-based models and methods . Still aiming at a protein family, Tobi developed an ENM-based method to make a function classification for globin family members based on their dynamics’ similarity . Besides, in 2020, an insightful review by Bahar et al revealed the evolutionary constraints on structure dynamics of a protein family to achieve the required functions: the slowest motion modes are conserved by a protein family for the common function; the low-to-intermediate frequency (LTIF) modes reflect the function specificity across family members; the fastest frequency modes ensure the core stability, which is the basics of functional specialization …”
Section: Introductionmentioning
confidence: 99%